Restructuring Electoral Cycles: Remedial Calibration and Legislative Discretion in Indonesia’s Constitutional Court Decision No. 135/PUU-XXII/2024 - Lisma Lisma; Lukman Ansar; Sabar Podu; Wira Kafryawan; Satriadi; Tarmizi; David Aprizon Putra (IAIN Bone, 2026)
Constitutional Court Decision No. 135/PUU-XXII/2024 restructures Indonesia’s electoral system by separating national and subnational elections and prescribing an interval of between two and two and a half years. This article evaluates the constitutional legitimacy of that intervention through doctrinal constitutional research and functional comparison. It develops a two-level framework distinguishing structural justification from remedial calibration. The analysis finds that the Court had a defensible constitutional basis for separating the two electoral cycles, given concerns relating to popular sovereignty, electoral quality, institutional capacity, political recruitment, and legislative inertia. However, the judgment provides a weaker constitutional and evidential basis for prescribing the precise temporal interval. It does not sufficiently explain why the selected minimum and maximum periods were necessary or why less intrusive remedies preserving greater legislative discretion would have been inadequate. The article argues that open legal policy neither immunises electoral legislation from review nor permits complete judicial displacement of legislative choice. Legitimate constitutional remedies must remain proportionate, evidence-based, and attentive to institutional competence.